2017
DOI: 10.1002/1873-3468.12798
|View full text |Cite
|
Sign up to set email alerts
|

Mouse acidic mammalian chitinase exhibits transglycosylation activity at somatic tissue pH

Abstract: Mouse acidic mammalian chitinase (AMCase) degrades chitin with highest efficiency at pH 2.0 and is active up to pH 8.0. Here, we report that mouse AMCase also exhibits transglycosylation activity under neutral conditions. We incubated natural and artificial chitin substrates with mouse AMCase at pH 2.0 or 7.0 and analyzed the resulting oligomers using an improved method of fluorescence-assisted carbohydrate electrophoresis. Mouse AMCase produces primarily dimers of N-acetyl-d-glucosamine [(GlcNAc) ] under both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Similar to chitotriosidase the other active chitinase in mammals and also a GH18 chitinase, we observe an apparent reduction in the rate of mAMCase catalysis across all pH values measured at 4MU-chitobioside concentrations above 80 μM, which suggests that mAMCase may be subject to product inhibition 22 . The underlying mechanism for the observed product inhibition may be that mAMCase can transglycosylate the products, as has been previously observed at pH 2.0 and 7.0 23 . This potential product inhibition leads to a systematic underprediction of rates by the Michaelis-Menten model at high substrate concentrations.…”
Section: Resultssupporting
confidence: 53%
“…Similar to chitotriosidase the other active chitinase in mammals and also a GH18 chitinase, we observe an apparent reduction in the rate of mAMCase catalysis across all pH values measured at 4MU-chitobioside concentrations above 80 μM, which suggests that mAMCase may be subject to product inhibition 22 . The underlying mechanism for the observed product inhibition may be that mAMCase can transglycosylate the products, as has been previously observed at pH 2.0 and 7.0 23 . This potential product inhibition leads to a systematic underprediction of rates by the Michaelis-Menten model at high substrate concentrations.…”
Section: Resultssupporting
confidence: 53%
“…Furthermore, supplementation of chitooligosaccharides can enhance the immune Interestingly, DD of the random-type chitosan affected the pH-dependence of the degradation rate (Figure 4A,B). We have previously reported that mouse Chia shows higher transglycosylation and weaker glycosidase activity under neutral conditions than at acidic pH [32]. Importantly, substrate degradation and transglycosylation by Chia can occur simultaneously.…”
Section: R Peer Review 8 Of 13mentioning
confidence: 95%
“…This method can separate and detect very low amounts (~pmol) of chitooligosaccharides according to their molecular weight, based on their differential migration rates through polyacrylamide gel [30,54,55]. The samples were quantified using the Luminescent Image Analyzer (Image-Quant LAS 4000, GE Healthcare, Piscataway, NJ, USA) as described previously [30,32,55].…”
Section: Analysis Of Chitooligosaccharides By Facementioning
confidence: 99%
See 1 more Smart Citation
“…Lysozyme TG was also applied to the synthesis of novel inhibitors for hen egg-white lysozyme [ 55 ] and a plant elicitor-active oligosaccharides [ 56 ]. Like lysozyme, chitinases belonging to the GH18 family were reported to catalyze TG reactions with COSs [ 57 , 58 , 59 ]. In these enzymatic TG reactions, native enzymes with full intrinsic hydrolytic activities were used.…”
Section: Synthetic Strategies Of Coss With Promising Functionsmentioning
confidence: 99%